IMPACT OF BLACK WATER TOURISM ON LOCAL COMMUNITIES IN KERENG BANGKIRAI PALANGKA RAYA - Tangkasiang, Yos Andy; Wurdianto, Kukuh; Aprilyansyah, Mahdi Surya; Ugang, Yandi (FISIPOL Universitas PGRI Palangka Raya, 2025)
Black Water Tourism in Kereng Bangkirai, Palangka Raya, has become a tourist destination that attracts the attention of both local and foreign tourists. With its stunning natural beauty and rich ecosystem potential, this place not only offers a recreational experience, but also has a significant social impact on the local community. This research aims to explore the social impact of Black Water tourism on the surrounding community, including economic, cultural and environmental aspects. Through data analysis and interviews with local communities, this research found that although there are clear economic benefits, there are also challenges that local communities must face in maintaining their identity and environmental sustainability.